2002
DOI: 10.1096/fj.02-0260rev
|View full text |Cite
|
Sign up to set email alerts
|

Does the coronary risk factor low density lipoprotein alter growth and signaling in vascular smooth muscle cells?

Abstract: There is increasing evidence that hypertension promotes low density lipoprotein (LDL) transportation into the subendothelial space of the vascular wall. Vascular smooth muscle cell (VSMC) proliferation plays an important role in the development and progression of cardiovascular diseases. Recently, several studies have demonstrated that LDL acts as a classic growth factor promoting VSMC growth via mitogenic signals normally elicited by classic growth factors. The present work summarizes current nontraditional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 161 publications
1
20
0
Order By: Relevance
“…Receptors belonging to the family of G proteincoupled receptors are potential mediators of LDL-induced MAPK pathway activation (3). In particular, it has been suggested that the presence of lysophosphatidic acid, plateletactivating factor, or lysophosphatidylcholine in LDL particles could induce signals in cells by activating the Edg G protein-coupled receptors (3). Because the first two of these compounds are, in principle, only found in oxidized LDLs (3) and because oxidation seems not to be a prerequisite for LDL stimulation of p38 MAPKs (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Receptors belonging to the family of G proteincoupled receptors are potential mediators of LDL-induced MAPK pathway activation (3). In particular, it has been suggested that the presence of lysophosphatidic acid, plateletactivating factor, or lysophosphatidylcholine in LDL particles could induce signals in cells by activating the Edg G protein-coupled receptors (3). Because the first two of these compounds are, in principle, only found in oxidized LDLs (3) and because oxidation seems not to be a prerequisite for LDL stimulation of p38 MAPKs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They may, however, have functions in addition to transporting cholesterol. For example, they seem to produce a mitogenic effect on endothelial cells, smooth muscle cells, and fibroblasts, and induce growthfactor production, chemotaxis, cell proliferation, and cytotoxicity (3). Moreover, an increase of LDL plasma concentration, which is observed during the development of atherosclerosis, can activate various mitogen-activated protein kinase (MAPK) pathways, including the two stressactivated protein kinase (SAPK) pathways, the c-Jun N-terminal kinase (JNK) and the p38 MAPK pathways (3)(4)(5).…”
mentioning
confidence: 99%
“…Besides their function as cholesterol carriers, LDLs have the potential to activate different intracellular signaling pathways such as the p38, the c-Jun N-terminal kinase (JNK) and the extracellular signal-regulated kinase (ERK) MAPKs, protein kinase C (PKC), G-proteins and cAMP (Gouni-Berthold and Sachinidis, 2002). The implication of these various cellular pathways in the physiological and pathological functions of LDLs is unclear at the present time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, LDLs induce activation of the p38 MAPKs in human umbilical vein endothelial cells (HUVEC) (Zhu et al, 2001), vascular smooth muscle cells (VSMC) (Gouni-Berthold et al, 2001;Gouni-Berthold and Sachinidis, 2002), and fibroblasts (Dobreva et al, 2003). Activation of the p38 MAPK pathway was shown to be important for the upregulation of endothelial genes implicated in atherogenesis (Zhu et al, 2001), VSMC growth (Gouni-Berthold et al, 2001;Gouni-Berthold and Sachinidis, 2002), and fibroblast spreading (Dobreva et al, 2003), mechanisms that could be potentially involved in the complications of atherosclerosis. Relatively little is known however on the mechanisms that allow LDLs to activate the p38 MAPK pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Proliferation of neointimal SMC and production of extracellular matrix proteins by these cells result in the formation of a fibrous cap overlying the prothrombotic lipid-rich core of the atherosclerotic plaque (11). Growth factors, such as platelet-derived growth factor (PDGF) and basic fibroblast growth factor (bFGF), are thought to be largely responsible for the accumulation of SMC in the intima (8,10,14). Coombes et al reported that C. pneumoniae infection of endothelial cells increases the expression of PDGF-BB (PDGF containing two B chains), which may contribute to the intimal thickening of aortic tissue in Chlamydia-infected rabbits (4).…”
mentioning
confidence: 99%